Screening History in 313 Cases of Invasive Cancer: A Retrospective Review of Cervical Cancer Screening in Alberta, Canada. Issue 1 (January 2017) - Mema, Silvina C.; Nation, Jill; Yang, Huiming; Waghray, Ranjit; Sun, Maggie C.; Xu, Linan; Kliewer, Gordon
Abstract : Objective: To examine the screening history of invasive cervical cancer (ICC) cases in Alberta, Canada to identify areas for improvement of the population-based cervical cancer screening program. Methods: Retrospective review of ICC cases diagnosed in 2 cities in Alberta between 2007 and 2012. Cancer morphology and staging were elicited from the Alberta Cancer Registry; cancer screening history and Pap test results were extracted from the Provincial Cervical Cancer Screening database. Women were classified as adequately screened, underscreened, and unscreened depending on time from last screening Pap test to diagnosis. Results: Of the 280 cases that occurred in women eligible for screening, 125 (44.6%) were adequately screened, 18 (6.4%) were underscreened, and 137 (49%) were unscreened. Among the adequately screened, 71 (56.8%) had normal Pap test results, but 48 (38%) had less than 3 previous Pap tests ( p = .003). Cancer stages I to II were diagnosed in 48.8% and 44.1% of adequately screened and unscreened women and cancer stages III to IV in 30.6% and 66.1% in each group, respectively ( p = .0058). Squamous cell carcinoma (SCC) was diagnosed in 189 women (67.5%). The proportion of SCCs was similar in adequately screened and unscreened women. Conclusions: The proportion of SCCs and advanced stages of ICC seems to be decreased. The results of quality improvement initiatives such as enhanced surveillance of high-grade Pap test results and histology-cytology correlation will be monitored and are expected to result in better outcomes for adequately screened women. Abstract : Retrospective review of invasive cervical cancer in adequately screened women elicits the effect of population-based screening and pinpoints areas for program improvement.